Época de semeadura e local de produção na germinação de sementes do algodoeiro - Pereira, Marcelo Oliveira (2012)
The place where cotton-plant is cultivated to produce seeds and its sowing time are extremely important, especially due to local climatic conditions. Based on this premise, this work aimed at verifying the influence distinct epochs of sowing in two different places had on the germination of cottonseed genotypes in the season 2007/2008. This study was carried out in two municipalities: Itumbiara, Goiás state, and Uberlândia, Minas Gerais state. Sowing of DeltaOpal, NuOpal, DP90B, DP604B, and Delta Penta genotypes seeds took place in the first half of November and in this first and second half of December. The experimental design was completely randomized in split plot with six replications. Evaluation included genotypes in the plots and sowing epochs in the subplots. After being manually harvested, cottonseeds were processed, delinted with sulfuric acid and then subjected to germination test to verify normal and abnormal (deformed, damaged and deteriorated) seedlings as well as dead seeds. Results statistical analysis allow concluding that in Itumbiara the first and second half of December are the best sowing time to produce cottonseeds from genotypes NuOpal, DP604G, and DP90B; while in Uberlândia the best sowing time were the second half of November and first half of December, no matter the genotype used.